The infective endocarditis of synthetic patch after left ventricle reconstruction (Dor procedure) - I. I. Chernov; S. T. Enginoev; D. Y. Kozmin; D. G. Tarasov (Российский кардиологический журнал)
Infective endocarditis (IE) has become an increasingly significant problem in cardiology and cardiac surgery over the past 30 years. Despite the noticeable progress made in the diagnosis and treatment of IE, the prognosis for this condition is still poor and the mortality rate reaches 15-30% [1, 2]. The risk of developing IE is especially high in patients with «intracardiac» artificial materials (artificial valves, prostheses of any type, implantable antiarrhythmic devices). This article presents a rare clinical case of   IE of synthetic patch after left ventricle reconstruction (Dor procedure).